Analyzing the Impact of COVID‐19 on the Mental Health of Students - Syed Nafiul Shefat; Nyme Ahmed; Rifat- Ibn-Alam; Dr. Md Taimur Ahad (International Journal of Computer and Information System (IJCIS), 2023)
Mental health is a state of well-being in which a person knows what he or she is good at, can deal with the normal stresses of life, can work well, and can make a positive difference in the world. In COVID-19 pandemic many challenges has been arise to students, educators, and parents. The difficulties and restrictions connected with the epidemic have increased the likelihood that students would suffer mental health problems, which may have a negative impact on their academic performance, social connections, and future career and personal chances. In this study, we analysis the factors which are affected the student’s mental health in Covid-19. An online survey that included demographics, lifestyle, and preferences in daily life, Behavioral questions, relevant to COVID-19, and standardized measures of depression, anxiety, resilience, and quality of life was completed by students from different universities of Bangladesh. Decision tree algorithm also applied in WEKA software tools. From the analysis we find that Disruption in education is the most impacting factor than other factors.Mental health is a state of well-being in which a person knows what he or she is good at, can deal with the normal stresses of life, can work well, and can make a positive difference in the world. In COVID-19 pandemic many challenges has been arise to students, educators, and parents. The difficulties and restrictions connected with the epidemic have increased the likelihood that students would suffer mental health problems, which may have a negative impact on their academic performance, social connections, and future career and personal chances. In this study, we analysis the factors which are affected the student’s mental health in Covid-19. An online survey that included demographics, lifestyle, and preferences in daily life, Behavioral questions, relevant to COVID-19, and standardized measures of depression, anxiety, resilience, and quality of life was completed by students from different universities of Bangladesh. Decision tree algorithm also applied in WEKA software tools. From the analysis we find that Disruption in education is the most impacting factor than other factors.